DIGITAL FILTERS INTENDED FOR PULSE SIGNAL PERIODS: n/a (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This work describes a new kind of FIR digital filter intended for the filtering of the pulse signal periods. This kind of digital filter was designed using the frequency locked loops (FLL), which are based on the time measurement and processing of the input periods only. FLL is a linear discrete system. Starting from the general form of differential equation of FLL, the transfer functions of FLL and Z transform of the FLL outputs are developed for FLL of any order. The main part of the article is devoted to describing how to design the appropriate FIR digital filter using an FLL of any order. Although the FIR digital filters and FLLs are different systems, for this purpose the theory of FIR digital filter and the corresponding MATLAB tools are used. Filtering abilities of the fifth-order FLL are demonstrated. The mathematical analyzes were performed using the Z transform approach. Analysis of FLL of the fifth-order was performed in the time and frequency domain. Computer simulation of FLL of the fifth-order is made in the time domain to enable precise insight into its properties.
Keywords: Frequency locked loop; Digital filter; Phase-locked loop; Digital circuit; Discrete linear system